2009
DOI: 10.1016/j.jcmg.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenosine and a Selective A2A Adenosine Receptor Agonist on Hemodynamic and Thallium-201 and Technetium-99m–SestaMIBI Biodistribution and Kinetics

Abstract: The bolus administration of regadenoson produced a hyperemic response comparable to a standard infusion of adenosine. The biodistribution and clearance of both (201)Tl and (99m)Tc-sestaMIBI during regadenoson were similar to adenosine vasodilation. Ex vivo perfusion images under the most ideal conditions permitted detection of a critical stenosis, although (201)Tl offered significant advantages over (99m)Tc-sestaMIBI for perfusion imaging during regadenoson vasodilator stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 23 publications
1
42
1
Order By: Relevance
“…19 Regadenoson (2.5 lg/kg IV bolus) and adenosine (4.5-minute infusion at 280 lg/kg) were studied in anesthetized dogs. 20 The biodistribution and clearance of 201-Tl and 99m-Tc sestamibi tracers and the hyperemic responses were comparable between regadenoson and adenosine. 20 During regadenoson stress, the relative microsphere flow deficit (0.34% ± 0.02%) was significantly greater than the relative perfusion defect with 201-Tl (0.53% ± 0.02%, P \ .001) or 99m-Tc sestamibi (0.69% ± 0.03%, P \ .001) and the ex vivo single photon emission computed tomography (SPECT) perfusion defect score was larger with 201-Tl (22% ± 2.8%) than with 99m-Tc sestamibi (17% ± 1.7%).…”
Section: Coronary Vasodilatationmentioning
confidence: 85%
See 1 more Smart Citation
“…19 Regadenoson (2.5 lg/kg IV bolus) and adenosine (4.5-minute infusion at 280 lg/kg) were studied in anesthetized dogs. 20 The biodistribution and clearance of 201-Tl and 99m-Tc sestamibi tracers and the hyperemic responses were comparable between regadenoson and adenosine. 20 During regadenoson stress, the relative microsphere flow deficit (0.34% ± 0.02%) was significantly greater than the relative perfusion defect with 201-Tl (0.53% ± 0.02%, P \ .001) or 99m-Tc sestamibi (0.69% ± 0.03%, P \ .001) and the ex vivo single photon emission computed tomography (SPECT) perfusion defect score was larger with 201-Tl (22% ± 2.8%) than with 99m-Tc sestamibi (17% ± 1.7%).…”
Section: Coronary Vasodilatationmentioning
confidence: 85%
“…20 During regadenoson stress, the relative microsphere flow deficit (0.34% ± 0.02%) was significantly greater than the relative perfusion defect with 201-Tl (0.53% ± 0.02%, P \ .001) or 99m-Tc sestamibi (0.69% ± 0.03%, P \ .001) and the ex vivo single photon emission computed tomography (SPECT) perfusion defect score was larger with 201-Tl (22% ± 2.8%) than with 99m-Tc sestamibi (17% ± 1.7%). 20 Binodenoson (0.1-3 lg/kg/minute infused for 10 minutes) produced dose-related vasodilatation in the left anterior descending (LAD) and left circumflex (LCx) arteries of 5 dogs without altering mean BP, HR, left atrial pressure, or left ventricular (LV) dP/ dt. 21 Infusion of adenosine at 300 lg/kg/minute for 4 minutes to the same dogs produced coronary vasodilatation that was limited by significant hypotension.…”
Section: Coronary Vasodilatationmentioning
confidence: 99%
“…regadenoson were 2.5 and 1.4 minutes, respectively, suggesting that the duration of coronary vasodilation produced by the drug combination of regadenoson and metoprolol may be suitable for distribution and clearance of the two radiotracers. 13 Metoprolol is a b 1 -adrenergic receptor antagonist indicated for the treatment of hypertension, angina, and stable heart failure. The dose (1.5 mg/kg) used in this study is an initial dose for the treatment of hypertension in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recent work by Timothy M. Bateman et al suggested an even longer delay from 60 up to 120 seconds to induce maximal hyperemia with regadenoson stress prior to radiotracer injection, leading to optimization of absolute MBF quantitation by PET. 25 Additional work further addressed concerns for dynamic PET imaging studies not only of the timing of regadenoson injection, but also its duration, 26,27 determining that increasing the regadenoson injection duration to 30 seconds in a canine preclinical study produced a more stable peak hyperemic response, comparable to the one achieved by a standard adenosine infusion. In the present study, despite likely achieving submaximal hyperemia with a standard protocol of regadenoson administration, the authors were able to demonstrate significant differences in CFR with an intermediate-risk CAD group, which would have likely been further accentuated had they included a low-risk CAD group.…”
Section: See Related Article Pp 1134-1144mentioning
confidence: 99%